Rigidity versus adaptation: contribution to the debate on agricultural viability and forest sustainability in southern Cameroon - Oyono, P.R.; Mala, W.A.; Tonye, J. (2003)
The Congo Basin is marked by the historical and cultural persistence, and resilience, of slash-and-burn agriculture – also known as shifting cultivation (or ‘forest agriculture’), on the one hand, and by contradictions between the relevance of externally introduced agricultural technologies and the implementation of productive agricultural mosaics, on the other. This paper examines these dynamics, insofar as they significantly influence the interface between forest and the ‘cultivated space’. In the light of Southern Cameroon’s case, and on the basis of theory, field observation, and discussions with the various actors, the paper explores the socio-cultural roots of slash-and-burn practices and draws up a typology of conceptual and scientific responses to the dilemma it represents for research, for land managers and for policy-making. Moreover, the paper shows that the articulation of agricultural cycles to agro-ecological units is evolving towards an integrated "agro-forestry" formula combining at the same time domestic fruit trees, food crops and non domesticated resources (forest trees and other forest products). These variables must be reconsidered in the design and the development of sustainable agro-ecological units based on a peaceful interaction and a progressive compromise between local communities’ vision of agricultural mosaics and the scientific effort stimulated by the absolute introduction of alternative solutions to slash-and-burn agriculture.